Holomental: Improving Mental Rotation Ability with Mixed Reality - Piri, Zeynep; Kaplan, Göknur; Cagiltay, Bilgehan; Cagiltay, Kursat (ACM, 2024)
Mental rotation ability is a type of spatial skill that is important in many aspects of life. With technological advancements, 3-D visualizations are more frequently used for addressing this spatial ability. In this study, we investigated the effectiveness of a Mixed Reality-based training module, Holomental, on Microsoft HoloLens 2 in improving the mental rotation ability of 22 understudents. The results showed that the training improved the accuracy of the students' responses by approximately 33%. Gender difference present before the training seemed to disappear after the training. The study contributes to our understanding of performance in Mixed Reality-based training.
Keywords: spatial ability; cognitive load; immersive experience; Microsoft HoloLens 2; mixed reality; 10. No inequality